Factors Related to Menstrual Hygiene Behavior of Adolescents in Indonesia: Systematic Review - Nudy Purwanto, Putri; Budi Amalia, Rize; Dewanti, Linda (Rifa'Institute, 2022)
Background: Menstrual hygiene is a component of personal hygiene (personal hygiene), which plays an important role in determining the health status, in order to avoid infection of the reproductive organs. Behaviour menstrual hygiene Pooris one of the main causes of morbidity in adolescents and if not handled properly will have an impact on reproductive health problems. The purpose of this study was to analyses the factors associated with adolescent behaviour menstrual hygiene in Indonesia. Methods: This study uses a systematic review by reviewing the literature obtained from four databases, namely PubMed, Science Direct, Scopus, and Google Scholar. Results are reported in the PRISMA diagram. Inclusion criteria included literature examining factors menstrual hygiene in Indonesia, adolescents aged 10-19 years, literature in English and Indonesian, full text and open access literature, published literature from the last 10 years (2011-2021), adolescents aged 10 -19 years, the EPHPP (Effective Public Health Practice Project) literature was used to assess the quality of the literature. Results: There were 18 literatures that met the inclusion and exclusion criteria. There is no relationship between biological factors, namely the age of menarche (n= 3, 100%) with behaviour menstrual hygiene in adolescents in Indonesia. There is a relationship between individual factors, namely knowledge (n = 9, 69.2%) and attitudes (n = 8, 80%), interpersonal factors (family support (n = 6, 75%, friend support (n = 4, 50%, teacher support (n= 3, 100%), support for health workers (n= 2, 100%), and mass media support n=3,100%) with behaviour menstrual hygiene in adolescents in Indonesia Conclusion: The importance of support from parents, friends , teachers, health workers to increase adolescent knowledge about behaviour menstrual hygiene and the availability of facilities and infrastructure that support behaviour menstrual hygiene in adolescents Key words: Menstrual hygiene factors, adolescents, Indonesia